Pediatric Case of Autoimmune Cerebellitis with Positive Anti-GAD Antibodies and Accidental Finding of Roth Spots - Hajatmena Alkhedir; Shahda Skaff; Abdelmoneim Mahgoub (Dr. Sulaiman Al Habib Medical Journal)
We present a pediatric case of autoimmune cerebellitis, which was distinguished by the presence of positive anti-glutamic acid decarboxylase (anti-GAD) antibodies. The patient, a young child, presented with a four-day history of progressively worsening headaches, coupled with persistent vomiting. These symptoms prompted immediate medical evaluation. Initial computed tomography (CT) imaging revealed a hypodense area in the left cerebellum and mild hydrocephalus, indicating fluid accumulation in the brain. Subsequent magnetic resonance imaging (MRI) provided more detailed visualization, confirming the diagnosis of acute cerebellitis, which was characterized by bilateral enlargement of the cerebellum and an associated mass effect that exerted pressure on the adjacent brain structures. The medical team initiated a comprehensive treatment regimen that included antibiotics to address any potential bacterial infection, antivirals to counter possible viral etiologies, immunoglobulin therapy to modulate the immune response, and corticosteroids to reduce inflammation. The patient responded well to this treatment protocol, with follow-up imaging showing a significant reduction in cerebellar swelling and overall improvement in clinical symptoms. The detection of elevated anti-GAD antibodies, along with anti-thyroglobulin antibodies, indicated an autoimmune origin of the cerebellitis. This autoimmune response can lead to the body’s immune system mistakenly attacking healthy brain tissue. Moreover, the incidental finding of a Roth spot, a retinal hemorrhage with a white center, during a routine eye examination suggested potential systemic involvement, possibly indicating a broader immune-mediated condition.